Acanthonyx petiverii H. Milne Edwards 1834 ... - In, First Published (Zenodo, 2022)
Acanthonyx petiverii H. Milne Edwards, 1834 (Figs. 11B, C, 12A–C, 13A–D) Acanthonyx petiverii H. Milne Edwards, 1834: 343 [Type locality: Antilles]. Peltinia scutiformis Dana, 1851a: 273. Dana (1855) [Atlas]: pl. 5, fig. 7a–c [Type locality: port of Rio de Janeiro]. Acanthonyx dissimulatus Coelho in Coelho & Torres, 1993: 231, fig. 1 [Type locality: Tambaú, João Pessoa, Paraíba]. Trindade and Martin Vaz specimens. 1 male (MZUSP 40595), 1 male juvenile (MZUSP 40671), Brazil, off Espírito Santo, Trindade Island, Parcel das Tartarugas, 20°31’11.6”S, 29°18’0.6”W, J.B. Mendonça coll., 18.xi.2017, tide pool, 1.5 m. 1 male (MZUSP 40192), ibidem, 20°31’10.4”S, 29°17’58.4”W, J.B. Mendonça coll., 3.viii.2018, 1.0 m. 1 male (39663), ibidem, 19.vi.2016, 1 m. 1 male (MZUSP 40190), ibidem, 20°31’11.6”S, 29°18’0.6”W, J.B. Mendonça coll., 18.xi.2017, 1.5 m. 4 males, 5 ovigerous females (MZUSP 40201), 1 ovigerous female (MZUSP 40191), 1 juvenile female (MZUSP 40615), ibidem, 20°31’11.6”S, 29°18’0.6”W, J.B. Mendonça ... : Published as part of In, First Published, 2022, Brachyuran crabs (Crustacea, Decapoda) from the remote oceanic Archipelago Trindade and Martin Vaz, South Atlantic Ocean, pp. 1-129 in Zootaxa 5146 on pages 26-30, DOI: 10.11646/zootaxa.5146.1.1, http://zenodo.org/record/7626155 ...